An Imperfect Marker: SLE and TTP-Like MAHA Without Low ADAMTS13 - Neha V. Chiruvolu DO, MS; Jonathan Scott MD, MPP; Sam S. Yeh MD (SAGE Publishing, 2021)
Thrombotic thrombocytopenic purpura (TTP) is a potentially fatal condition that can be challenging for clinicians to identify in the setting of autoimmune diseases such as systemic lupus erythematosus (SLE). This difficulty is compounded when a patient presents with all of the clinical signs of a TTP-like microangiopathy, however, with near normal ADAMTS13. This case report describes a 44-year-old female with a history of SLE who was hospitalized with acute on chronic anemia, thrombocytopenia, and altered mental status. The patient's ADAMTS13 was mildly low; hence, she was initially treated for SLE-associated immune thrombocytopenic purpura without any clinical response. The patient then underwent plasmapheresis (plasma exchange [PLEX]) for treatment of a suspected TTP-like microangiopathy. She responded to PLEX with improvement in her platelet count and mental status. This case illustrates the importance of considering TTP-like microangiopathic hemolytic anemia in the differential for patients with a history of SLE presenting with clinical signs of TTP even in the setting of near-normal ADAMTS13, thus warranting prompt treatment with PLEX.